Synthesis and Photo/Radiation Chemical Characterization of a New Redox-Stable Pyridine-Triazole Ligand - Al-Romema, Abdulaziz; Plass, Fabian; Nizovtsev, Alexey; Kahnt, Axel; Tsogoeva, Svetlana (ChemPhysChem, 2024)
Photocatalysis using transition-metal complexes is widely considered the future of effective and affordable clean-air technology. In particular, redox-stable, easily accessible ligands are decisive. Here, we report a straightforward and facile synthesis of a new highly stable 2,6-bis(triazolyl)pyridine ligand, containing a nitrile moiety as a masked anchoring group, using copper(I)-catalyzed azide-alkyne cycloaddition (CuAAC) click reaction. The reported structure mimics the binding motif of uneasy to synthesize ligands. Pulse radiolysis under oxidizing and reducing conditions provided evidence for the high stability of the formed radical cation and radical anion 2,6-di(1,2,3-triazol-1-yl)-pyridine compound, thus indicating the feasibility of utilizing this as a ligand for redox active metal complexes and the sensitization of metal-oxide semiconductors (e. g., TiO2 nanoparticles or nanotubes).
CRIS-Team Scopus Importer:2024-08-02
Keywords: click chemistry; laser photolysis; pulse radiolysis; pyridine-triazole; redox-stable ligand